Circuit-based method for extracting the resistive leakage current of metal oxide surge arrester - Amir Hesam Khavari; Abdullah Munir; Zulkurnain Abdul- Malek (Bulletin of Electrical Engineering and Informatics, 2020)
Resistive leakage current based condition assessment of metal oxide surge arrester (MOSA) is one of the most extensively employed technique to monitor its degradation. An extraction method is customarily required to extract the resistive component from the total leakage current. The existing methods to extract the resistive current are complex and less accurate. Therefore, this paper describes a simple and accurate circuit-based method to extract the resistive current using equivalent model and measured leakage current of the arrester. The accuracy of the proposed method is validated through experimental results on ABB’s 120 kV surge arrester, EMTP and QuickField software simulations. The performance of the method is also analyzed and verified experimentally on 72, 180 and 240 kV rated ABB’s surge arresters. The obtained results of resistive leakage current have shown the maximum error of 0.001%. Simple and easier computational steps with higher accuracy are the key benefits of the proposed technique.